4/(5y-25)+1=-8/(y-5)

Simple and best practice solution for 4/(5y-25)+1=-8/(y-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4/(5y-25)+1=-8/(y-5) equation:


D( y )

y-5 = 0

5*y-25 = 0

y-5 = 0

y-5 = 0

y-5 = 0 // + 5

y = 5

5*y-25 = 0

5*y-25 = 0

5*y-25 = 0 // + 25

5*y = 25 // : 5

y = 25/5

y = 5

y in (-oo:5) U (5:+oo)

4/(5*y-25)+1 = -8/(y-5) // + -8/(y-5)

4/(5*y-25)-(-8/(y-5))+1 = 0

4/(5*y-25)+8*(y-5)^-1+1 = 0

4/(5*y-25)+8/(y-5)+1 = 0

(4*(y-5))/((5*y-25)*(y-5))+(8*(5*y-25))/((5*y-25)*(y-5))+(1*(5*y-25)*(y-5))/((5*y-25)*(y-5)) = 0

4*(y-5)+8*(5*y-25)+1*(5*y-25)*(y-5) = 0

5*y^2+44*y-50*y-220+125 = 0

5*y^2-6*y-95 = 0

5*y^2-6*y-95 = 0

5*y^2-6*y-95 = 0

DELTA = (-6)^2-(-95*4*5)

DELTA = 1936

DELTA > 0

y = (1936^(1/2)+6)/(2*5) or y = (6-1936^(1/2))/(2*5)

y = 5 or y = -19/5

(y+19/5)*(y-5) = 0

((y+19/5)*(y-5))/((5*y-25)*(y-5)) = 0

((y+19/5)*(y-5))/((5*y-25)*(y-5)) = 0 // * (5*y-25)*(y-5)

(y+19/5)*(y-5) = 0

( y+19/5 )

y+19/5 = 0 // - 19/5

y = -19/5

( y-5 )

y-5 = 0 // + 5

y = 5

y in { 5}

y = -19/5

See similar equations:

| 22+x=-8 | | 4/(5y-25)+1 | | 4xy+x=10 | | xy=8 | | 0.85m=-24 | | (5+u)(3u-2)=0 | | 7x^2+11xy-6y^2= | | x^2-24xy+63y^2= | | x^2+24xy+63y^2= | | (5x+8)/7=6 | | 19=7x-39 | | N+8=3n+20 | | gt=5g+5z | | 3(-6x+4/2+3)-5=25 | | 3(-6x+4+3)-5=25 | | 6x-8=.33333333(18x+24) | | (6x2+43x+39)/x+6 | | 100x^2-40+16= | | 2x^8-14x^6+4x^3/-2x^5 | | -9r+5=r-125 | | 8x^2+51x+54=0 | | x-0,2/0,1=1 | | (25p^-3m^20)/(35p^5m^4) | | 0.13-0.01(x+1)=0.03(4-x) | | (4n-3h)/13=C | | 3(x+3)/4=2x-3 | | 6y^2-6y-12=0 | | -35+7x=-7x-5(1x+7) | | (5/2*1/3+4/5*3/2)*15/2 | | 3(x-2)-10= | | 0.95x+0.05(10-x)=0.10(-139) | | 13+5r=4(1r+5) |

Equations solver categories